2007
DOI: 10.22358/jafs/66802/2007
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation with plant extracts, xantophylls and synthetic antixidants: Effect on fatty acid profile and oxidative stability of frozen stored chicken breast meat

Abstract: Chickens from 22 to 42 days of age were fed a basal diet supplemented with α-tocopheryl acetate (150 mg·kg -1 ), extracts of coneflower, thyme or sage (560 mg·kg -1 ), marigold xantophylls (20 mg lutein·kg -1 ), mix of synthetic antioxidants (48.6 mg·kg -1 ) or β-apo-8-carotenoic acid ethylester (40 mg·kg -1 ). On day 42 the chickens were slaughtered, breast muscles were excised, frozen (-20 o C) and stored for 6 months.Dietary supplementation with plant extracts, synthetic antioxidants or pigments did not aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 21 publications
1
21
0
3
Order By: Relevance
“…However, the added plants had a significantly positive effect on improving sensory quality of thigh samples after 12 months of freezing storage compared with control. Stored breast meat (6 months, -20°C) was found to be suitable for consumption, but the effect of additives (plant extracts of coneflower, thyme and sage) on the taste and smell of meat was not recorded (Koreleski and Świątkiewicz, 2007). Several authors stressed improved sensory characteristics of poultry meat after adding plants with antioxidant activity (Šperňáková et al, 2007;Marcinčák et al, 2008).…”
Section: Kgmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the added plants had a significantly positive effect on improving sensory quality of thigh samples after 12 months of freezing storage compared with control. Stored breast meat (6 months, -20°C) was found to be suitable for consumption, but the effect of additives (plant extracts of coneflower, thyme and sage) on the taste and smell of meat was not recorded (Koreleski and Świątkiewicz, 2007). Several authors stressed improved sensory characteristics of poultry meat after adding plants with antioxidant activity (Šperňáková et al, 2007;Marcinčák et al, 2008).…”
Section: Kgmentioning
confidence: 99%
“…Chicken meat containing higher amount of PUFAs is at risk that their profile will change during storage (Koreleski and Świątkiewicz, 2007). Using natural antioxidants in poultry fattening is a simple method to achieve a higher antioxidant stability, improvement of sensory properties (aroma and taste) and prolongation of storage (Windisch et al, 2008;Luna et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Dietary supplementation of natural extracts at doses around 0.5 g/kg feed resulted in preventing lipid oxidation (Lopez-Bote et al, 1998;Schiavone et al, 2007b) (Table 7). However, some authors reported no significant effects of the dietary extracts on the oxidative stability of poultry meat (Koreleski and Swiatkiewicz, 2007) and eggs (Galobart et al, 2001a) (Table 7). Dietary plant extracts of rosemary, grape, citrus, or marigold efficiently inhibited lipid oxidation in plasma of rats fed n-3 PUFA rich diets thus suggesting the phytochemicals in extracts can be absorbed and act as antioxidants (Gladine et al, 2007).…”
Section: Downloaded By [University Of Connecticut] At 12:47 07 Octobementioning
confidence: 99%
“…Similarly, Koreleski and Swiatkiewicz (2007) report the different effect of plant extracts feeding (sage and coneflower in the dose 560 mg) to the profile of fatty acids in breast muscle. Supplementation of the diet with sage extract increased the levels of stearic acid, arachidonic acid and n-3 PUFA and decreased the level of MUFA in comparison with control.…”
Section: Chemical Composition and Fatty Acid Analysis Of Meatmentioning
confidence: 99%